Gene-expression patterns during regeneration of the multi-organ complex after evisceration in the sea cucumber Eupentacta quinquesemita - Okada, Akari; Udagawa, Sumio; Kohtsuka, Hisanori; Hayashi, Yoshinobu; Miura, Toru (Frontiers in Marine Science, 2024)
Many species of sea cucumbers (Echinodermata, Holothuroidea) perform evisceration, i.e., ejection of internal organs including digestive tracts when responding to environmental stresses. After evisceration, they also show a high regenerative capacity, in which all the eviscerated organs regenerate. Especially in anterior evisceration species, the oral complex structure consisting of multiple organs, including the digestive tract and central nervous system, are reconstructed. The detailed developmental mechanisms underlying the process remains unclear, and therefore, in this study, focusing on Eupentacta quinquesemita, gene expression analyses in the regenerating tissues were carried out. For the formation of the gut tube, genes involved in mesenchymal-epithelial transition were upregulated consistently with the histological changes. Upregulation of Hox and Parahox genes along the anterior-posterior axis was observed, implying the involvement of these genes in the spatial differentiation of the digestive tract. In addition, the expression of otx, six and pax, i.e., transcription factors patterning anterior nervous tissues, was upregulated during the regeneration of the central nervous system. Taken together, these results suggest that conserved genes are co-opted to the internal organ regeneration after evisceration in sea cucumbers.